Beneficial effects of probiotic and phytobiotic as growth promoter alternative to antibiotic for safe broiler production - Ferdous, Md Faisal; Arefin, Md Shafiul; Rahman, Md Moshiur; Ripon, Md Mustafijur Rahman; Rashid, Md Harunur; Sultana, Mst Rokeya; Hossain, Muhammad Tofazzal; Ahammad, Muslah Uddin; Rafiq, Kazi (Journal of Advanced Veterinary and Animal Research, 2019)
Objectives: Drug residues in poultry products could lead to the development of antibiotic-resistant bacteria as in any living animal and human alike. Extensive use of antibiotics in animals to promote growth rate, increase feed efficiency, and for prevention of intestinal infections has led to the development of resistant bacteria in the gastrointestinal tract. The present study was conducted to evaluate the effects of biological supplementation of probiotic, phytobiotic, and their combination over antibiotic on growth performance, microbial load, and hematological parameters in Broiler. Materials and methods: Sixty-five broiler chicken were divided into five groups (12 birds in each group), namely, group A (basal diet), group B (antibiotic, Renamycin 100®), group C (phytobiotic, Galibiotic®), group D (probiotic, Bio-Top®), and group E (combination, Galibiotic®+Galibiotic®) and five were sacrificed for baseline data on day 0. Results: Average final live weight gain was highest in group D (probiotic) than other groups. The feed conversion ratio was highest in group A and lowest in the probiotic group (group C). Blood samples were collected on 14th and 28th day for hematological studies. The mean hematology values regarding the total erythrocyte count, hemoglobin concentration, packed cell volume, and erythrocyte sedimentation rate differed significantly (p < 0.05) among groups. The pH of all the treatment groups was significantly decreased compared to the control group (p < 0.05) where group C was significantly (p < 0.05) lower than all other groups. Highest total viable cell count was observed in control (group A) and total coliform count in phytobiotic (group C) was significantly lower than in other treatment groups (p < 0.05). Conclusion: It may conclude that biological supplements have a significant positive impact on growth performance, hematological parameters, and gut microbial load in broiler chicken of which the probiotic showing the best effects. Supplementation of probiotic in feed could be one of the best candidates as an alternative to antibiotics as growth promoter for safe broiler production. J. Adv. Vet. Anim. Res., 6(3): 409-415, September 2019